Teaching Quality and Democratic Behavior as Predictors of Students Engagement in Learning Science - Orcullo, Myla Joy Q.; Elesio, John Mart (PT FORMOSA CENDEKIA GLOBAL, 2024)
To teach students effectively, they must be engaged. This study investigated the combined significant influence of teaching quality and democratic behavior on students’ engagement in learning science. The study employed a non-experimental quantitative design using a descriptive-predictive technique. It utilized a total of 117 respondents from one of the private schools in Davao City who answered the adapted survey questionnaire. Using Mean, Pearson r, and Multiple Linear Regression the following findings were made: the level of teaching quality, teacher’s democratic behavior, and student engagement were high; teaching quality and student’s engagement have a significant relationship; teacher’s democratic behavior and student’s engagement have a significant relationship. Results implied that the indicators are oftentimes observed and significantly influenced students’ engagement. Furthermore, both teaching quality and democratic behavior have a combined significant influence on student’s scientific engagement. In conclusion, both variables have impact students' engagement in learning science. Thus, it is recommended that the two be utilized by the teachers to improve students’ engagement in science education.